INVOLVEMENT OF P4503A IN THE METABOLISM OF 7,8-BENZOFLAVONE BY HUMAN LIVER-MICROSOMES - LEE, HS; JIN, CB; CHONG, HS; YUN, CH; PARK, JS; KIM, DH (TAYLOR & FRANCIS LTD LONDON, 1994)
1. The metabolism of 7,8-benzoflavone (ANF) was studied in human liver microsomal fractions. Five metabolites were generated and tentatively identified as ANF 5,6-oxide, 5,6-dihydrodiol, 7,8-dihydrodiol, 6-hydroxy ANF, and 7-hydroxy ANF based on UV and mass spectral analysis. 2. The involvement of P4503A in the metabolism of ANF was confirmed by the following observations: (1) correlation of ANF 5,6-oxide formation was noted with testosterone 6 beta-hydroxylation, an indicator of P4503A, in human liver microsomal fractions; (2) metabolism of ANF was inhibited by various selective P4503A enzyme inhibitors; (3) rabbit antibody raised against P4503A4 inhibited the ANF metabolism by > 80%; and (4) microsomal fractions that specifically expressed P4503A4 metabolized ANF to oxidized metabolites. 3. These results indicate that P4503A isoform(s) mainly metabolize ANF to oxidized derivatives in human liver microsomal fractions.
Keywords: ALPHA-NAPHTHOFLAVONE; CYTOCHROME-P-450; INHIBITION; RAT; OXIDATION; INACTIVATION; HYDROXYLASE; ACTIVATION; FLAVONOIDS; ISOZYMES